Avances en la etiologia y manejo de la pudricion blanda de tallos de pitahaya, Hylocereus undatus H. (Cactaceae) - Valencia Botin, A.J.=700 1 Cruz Hernandez, P.; Rodriguez Canto, A.
(Es, En)
Ilus., 16 ref.
Keywords: HYLOCEREUS UNDATUS; PODREDUMBRES; CLONES; NUTRIENTES; CUBA; PUDRICION BLANDA